Dynamical Model for Transmission of West Nile Virus in Chicken-Mosquito Interaction - Jafaruddin Hamid; Juni Wijayanti Puspita; Nuning Nuraini; Edy Soewono (Institute for Research and Community Services (LPPM) ITB, 2014)
The West Nile virus (WNV) is transmitted through the bites of infected mosquitoes. The spread of WNV in chicken populations is quite unique. Although chickens can contract the virus through a mosquito bite, they immediately build immunity to the virus and do not show physical symptoms of illness and hence chickens are only temporary carriers of the virus. Recently, experimental results have shown that mosquitoes do not change fecundity behavior, yet results indicate that resistance to infection is associated with afitness cost in terms of mosquito survival. We constructed a host-vector type transmission model for WNV in mosquito-chicken populations. The basicreproductive ratio, Ro , was obtained. From sensitivity analysis of Ro it was shown that under certain conditions this ratio decrease